XRF analysis of base metals prepared by fused bead method - Engelbrecht, Chantelle (My University, 2012)
The objective of the study was to investigate the preparation of glass beads for base metal analysis of mining samples prior to x-ray fluorescence analysis. The research method used included the investigation of different fluxes, oxidising, non-wetting agents, fusion temperature and time. The experiments were carried out using different fusion instruments: Electrofluxer and Katanax followed by both EDXRF and WDXRF analysis. The x-ray spectrometers were calibrated with standards prepared from pure oxides and the results compared to values determined by alternative techniques. Different statistical methods were used to validate the experiments including factorial designs. Not all the elements and oxides were recovered successfully, however, perfect glass beads were prepared. The two areas of concern were addressed successfully: firstly the loss of copper was overcome by using an alternative heating mechanism of the Katanax and sodium iodide as the non-wetting agent. Secondly, the sulphur was successfully oxidised and retained in the glass beads.
M.Sc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: Chemistry; Fluorescence spectroscopy; X-ray spectroscopy